Size and Charge Evaluation of Standard Humic and Fulvic Acids as Crucial Factors to Determine Their Environmental Behavior and Impact - Klučáková, Martina (Frontiers in chemistry, 2018)
In this work, the size and charge of humic and fulvic standards purchased from the International Humic Substances Society are presented and discussed. The secondary structure of humic substances in water environment as well as the size and shape of the dissolved humic species and their changes are ill-defined, very dynamic and can be strongly affected by environmental conditions as the concentration, pH, and ionic strength. They have a strong propensity to aggregate which control their interactions with other components, mobility, and functioning in the environment. Particle size distributions were determined by means of dynamic light scattering, zeta potential by Doppler electrophoresis. The intensity, volume, and number particle size distribution were obtained. Two or three different size fractions were detected in the studied systems. Large macroparticles (>1 μm) were observed in the majority of them, mainly in the case of more concentrated solutions. Medium fractions of fulvic submicroparticles had higher average diameters (500-1,200 nm) than those in humic acids (300-600 nm). Small nanoparticles (<100 nm) were detected mainly in alkaline solutions. Fulvic acids with more functional groups (active sites) can form more easily bigger particles mainly in medium concentration region. Alkaline conditions supported the expansion of humic and fulvic coils and liberation of small particles from them. The colloidal stability, indicated by more negative zeta potentials, was higher for humic acids. In the case of fulvic acids, the colloidal stability increased with increasing pH as a result of the dissociation of their functional groups. The increase of particle size corresponded usually with higher stability.
Keywords: humic acids; stability; solubility; fulvic acids; charge; particle size